Pauci-Immune Crescentic Glomerulonephritis: An ANCA-Associated Vasculitis - Syed, Rafeel (Biomed Res Int, 2015)
Rapidly progressive glomerulonephritis (RPGN) is a syndrome signified by a precipitous loss of renal function, with features of glomerulonephritis including dysmorphic erythrocyturia and glomerular proteinuria. RPGN is associated with extensive crescent formation, and, thus, the clinical term RPGN is often used interchangeably with the pathologic term crescentic glomerulonephritis (CGN). From an immunopathologic standpoint, primary RPGN is divided into pauci-immune GN (PICG), anti-GBM GN, and immune complex GN. PICG, the most common etiology of primary RPGN, refers to a necrotizing glomerulonephritis with few or no immune deposits by immunofluorescence (IF) or electron microscopy (EM). In most patients, pauci-immune CGN is a component of a systemic small vessel vasculitis such as granulomatosis with polyangiitis (GPA). Approximately 90% of patients with PICG have circulating ANCA antibodies, leading to the nomenclature ANCA-associated vasculitis (AAV). Recent research has identified several other antibodies associated with PICG, which is now understood to be a complex spectrum of disease with considerable overlap in terms of clinical phenotype and outcomes. In addition, several genetic and environmental factors have recently been implicated in the pathogenesis of this disorder. With new prognostic classifications, enhanced understanding of immunopathologic mechanisms, and novel treatment paradigms, clinical and experimental interest in PICG remains high.